Caprine milk protein polymorphisms: Possible applications for African goat breeding and preliminary data in Red Sokoto - Ibeagha-Awemu, E.M.; Bemji, M.N.; Osinowo, O.A.; Chiatti, F.; Chessa, S.; Erhardt, G. (TSAP and ILRI, 2006)
About 70% of all milk consumed in sub-Saharan Africa is imported from other parts of the world. This trend may be reversed by encouraging production through marker assisted selection. Goats are second to cattle in milk production, they require less inputs and their small size make them attractive to smallholder production systems. This paper presents the current knowledge on milk protein polymorphisms in goats, including aS1-casein, aS2-casein, b-casein, k-casein, alactalbumin and b-lactoglobulin, and their relationships with milk quality, composition and technological properties. Moreover, the results of a preliminary investigation on milk samples from 48 Red Sokoto goats by isoelectrofocusing (IEF) are discussed. Three main alleles were detected at each of CSN1S1 and CSN1S2 loci and two IEF patterns at CSN3 locus. Finally, the paper makes recommendations for further exploitation of African goats for milk production considering the possibility for the genetic improvement of milk yield and composition, fulfilling both nutritional requirements and technological properties.